Exponential chaotic law of cardiac dynamic systems for Holter evaluation: 16 hours - Rodríguez, Javier (2017)
Introduction: In a previous study, a 16-hour reduction in the evaluation of the exponential law of chaotic cardiac dynamics was done, showing its effectiveness in the characterization of disease and normality. Objective: To confirm the clinical applicability of the exponential mathematical law to evaluate chaotic cardiac dynamics from the Holter registers in 16 hours, observing its diagnostic utility by reducing its evaluation time. Design: Cross-sectional observational study where the electrocardiographic parameters were evaluated using inductive mathematical methodologies with statistical confirmation. Methodology: 100 Holter records were taken with different types of pathology, and 40 Holter that were diagnosed as normal. For each Holter, a chaotic attractor was constructed, and measuring their spaces of occupation and fractal dimension, the mathematical evaluation to differentiate normality of disease was applied. Finally, measures of diagnostic concordance were made with respect to the gold standard. Results: The spatial occupation of all the attractors was within the expected values; the normal records had values in the grid between 205 y 423. For the records with acute disease, these values ranged from 21 y 65; and for chronic disease registries these values ranged from 104 y 195. The values of sensitivity and specificity were 100% and the Kappa coefficient was 1. Conclusion: The present study shows the clinical applicability of this methodology for the evaluation in 16 hours of continuous electrocardiographic or Holter registers.